Pengaruh Konsentrasi Sukrosa Terhadap Karakteristik Minuman Probiotik Sari Buah Naga Merah (Hylocereus polyrhizus) Terfermentasi dengan Isolat Lactobacillus sp. F213 - Dewi Cinderela, Ni Komang; Nocianitri, Komang Ayu; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i02.p03, 2022)
This research was aimed to determine the effect of sucrose on the characteristics of fermented red dragon fruit (Hylocereus polyrhizus) probiotic juice with Lactobacillus sp. F213 isolates and to determine the right concentration of sucrose that produced the best characteristics of fermented red dragon fruit probiotic juice. This research used a Completely Randomized Design (CRD) with a concentration of sucrose as treatments, which consisted of five levels: 0%, 3%, 6%, 9%, dan 12%. Each treatment was repeated 3 times to obtain 15 units of samples. The data of total LAB, total sugar, total acid, pH shown in the table and figures which analyzed descriptively. Sensory properties were analyzed by analysis of variance followed by Duncan Multiple Range Test  if the treatment has a significant effect. The results showed that the addition of sucrose concentration can increase the total LAB, total sugar, total acid and decrease pH. Concentration of sucrose affected taste (hedonic), sour taste (score), sweet taste (score), and overall acceptance (hedonic). The 9% sucrose concentration produced the best fermented red dragon fruit probiotic juice with the characteristics of total LAB 10.05 log CFU/ml, total sugar 13.52%, total acid 0.21%, pH 3.98, the color and the aroma were preferred, with slightly sour and sweet taste were preferred, and overall acceptance was preferred.